Let’s not steal equity from our patients in the name of quality - Hicks, Chelsea D.; Barnett, Heather; Shi, Jennifer; Velonjara, Julia; Kmail, Zaher; Vavilala, Monica S.; Lindo, Edwin G. (Frontiers in Public Health, 2025)
Healthcare can be, we believe, the vanguard to lead us to a more just society but has much work to do. Quality improvement (QI) processes drive care delivery based on metrics and reporting requirements, but equity is not a commonly used QI measure, and the extent of inequitable care affecting patients is unclear at best. While quality metrics can provide benchmarks for healthcare based on published evidence, quality metric standards that do not consider healthcare equity will not lead to the provision of equitable, patient-centered care. In fact, equity is separated from quality in most existing quality metric frameworks when, instead, achieving equity should be a central component of high-quality care. This is true even for leading health conditions, such as injury and violence. Yet, achieving equitable care is every patient’s right and achieving healthcare equity should be a societal and bedside goal. We call for alignment between patients, healthcare providers, and healthcare organizations to unite health equity and healthcare quality metrics. Finally, we offer some recommendations and an example of success in pursuing and operationalizing health equity.